Characterization of neuronal spiking patterns in the medial prefrontal cortex under varied general anesthetics in mice - Hu, Xiangyu; Jiang, Jingyao; Leng, Yu; Yang, Yaoxin; Zhang, Donghang; Li, Ke; Zhu, Tao; Liang, Peng; Zhou, Cheng (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Purpose The mechanisms underlying reversible unconsciousness induced by general anesthetics remain unclear. This study aimed to investigate the effects of four commonly used anesthetics on neuronal spiking patterns in layer 5 of the medial prefrontal cortex (mPFC). Methods In vivo multi-channel recordings were performed in layer 5 of the mPFC in a mouse model. Neuronal spiking patterns of regular-spiking and fast-spiking neurons were measured and compared across wakefulness loss of the righting reflex (LORR), and recovery of the righting reflex (RORR). Four anesthetic/sedative drugs (sevoflurane, propofol, ketamine, and dexmedetomidine) were tested. Results During LORR, most cortical regular-spiking neurons were inhibited, while a small subset was excited. Fast-spiking neurons exhibited significant suppression across all anesthetics. Among these, the firing rate of inhibited regular-spiking neurons was closely associated with the transitions between LORR and RORR. Sevoflurane, propofol, and dexmedetomidine exhibited similar modulatory effects on mPFC neurons, whereas ketamine induced stronger excitatory effects on both regular- and fast-spiking neurons. Conclusions Sevoflurane, propofol, and dexmedetomidine exert comparable effects on neuronal spiking in the mPFC, while ketamine induces distinct excitatory effects. Inhibited regular-spiking neurons in layer 5 of the mPFC are closely associated with the reversible transitions between LORR and RORR.